JOURNAL OF GOVERNMENT & POLITICS : Resources Exchange Model in Implementation Network of Fishermen Community Policy in Makassar City - Gita Susanti, Alwi (FISIPOL UMY, 2017)
Public policy implementation network is a study that tried to accumulate all the stakeholders as potential resources to determine and implement a public policy.